2002
DOI: 10.1063/1.1521724
|View full text |Cite
|
Sign up to set email alerts
|

The 248 nm photolysis of NO2/N2O4: Time-resolved Fourier transform infrared emission from NO and NO2, and quenching of NO (v=5–8)

Abstract: Photodissociation of gaseous CH3COSH at 248 nm by time-resolved Fourier-transform infrared emission spectroscopy: Observation of three dissociation channels J. Chem. Phys. 138, 014302 (2013); 10.1063/1.4768872 Gas-phase photodissociation of CH3COCN at 308 nm by time-resolved Fourier-transform infrared emission spectroscopy J. Chem. Phys. 136, 044302 (2012); 10.1063/1.3674166 I. Three-center versus four-center HCl-elimination in photolysis of vinyl chloride at 193 nm: Bimodal rotational distribution of HCl (v7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…The major features of the TRFTIR apparatus have been described previously 3,22 and are summarised here. A Lamba-Physik ArF 193 nm excimer laser, generating a 30 mJ pulse in approximately 1 cm 2 , was multipassed in a reaction cell containing either N 2 O or NO 2 (at typical pressures of 1 Torr and 0.1 Torr, respectively) and the quenching gas, together with added Ar, to ensure rotational thermalisation and prevent fly out of the excited species from the observed region.…”
Section: Methodsmentioning
confidence: 99%
“…The major features of the TRFTIR apparatus have been described previously 3,22 and are summarised here. A Lamba-Physik ArF 193 nm excimer laser, generating a 30 mJ pulse in approximately 1 cm 2 , was multipassed in a reaction cell containing either N 2 O or NO 2 (at typical pressures of 1 Torr and 0.1 Torr, respectively) and the quenching gas, together with added Ar, to ensure rotational thermalisation and prevent fly out of the excited species from the observed region.…”
Section: Methodsmentioning
confidence: 99%
“…The major features of the TRFTIR apparatus have been detailed previously 21,22 and are summarised here. A Lambda-Physik (Compex 102) ArF 193 nm excimer laser, operating at 10 Hz with an energy of 100 mJ per pulse and a beam of area 1 cm 2 photolysed the vinyl halide typically at pressures of 50-350 mTorr in the presence of excess Ar to ensure that rotational (but not vibrational) thermalisation of the photolysis products was complete on the time scale of the observations.…”
Section: Methodsmentioning
confidence: 99%
“…The results of studies of the photodissociation of a NO 2 molecule in the ultraviolet wavelength range were considered in [28,29]. It was shown that the distribution of NO fragments over vibrational states during fragmentation of the NO 2 molecule is inverted.…”
Section: Introductionmentioning
confidence: 99%